Metabolic adaptation and reticuloruminal pH in periparturient dairy cows experiencing different lipolysis early postpartum. (5th May 2016) - Humer, E.; Khol-Parisini, A.; Gruber, L.; Wittek, T.; Aschenbach, J. R.; Zebeli, Q.
Abstract : Metabolic adaptation includes an array of concerted metabolic and endocrine events that enable dairy cows bridging the period of energy deficit at the onset of lactation. The present study evaluated metabolic, endocrine and reticuloruminal pH changes in 30 (25 Holstein and five Simmental) periparturient dairy cows experiencing variable lipolysis early postpartum . Cows were fed the same close-up and fresh lactation diets and kept in the same management conditions. Blood samples were collected at day 14, and day 4, relative to expected parturition, and at day 2, and day 21 postpartum, and serum metabolites and hormones related to glucose and lipid metabolism, as well as concentrations of several liver enzymes and acute phase proteins were determined. Additionally, reticuloruminal pH was monitored every 10 min over the last 3 days of the observation period. BW and milk yields were recorded and balances of energy and protein were assessed. Based on serum concentration of non-esterified fatty acids (NEFA) postpartum, cows were retrospectively classified into low ( n =8), medium ( n =11), and high ( n =11) lipolysis groups, with NEFA levels of <0.4 mmol/l, between 0.4 and 0.7 mmol/l, and >0.7 mmol/l, respectively. Overall, elevated NEFA concentrations in the High group went along with a higher ratio of NEFA to cholesterol and reduced insulin sensitivity. While serum glucose, energy deficit and BW loss did not differ, cows of the High group exhibited increased lactate concentrations in the serum, compared with the Medium group. No differences in liver enzymes and acute phase proteins were evidenced among fat mobilization groups, whereas concentration of serum billirubin was lowest in the Low group after parturition. Data of milk yield and milk energy output showed no differences among groups, despite divergences in calculated energy balance and BW change postpartum . Cows of the Low group tended to increase dry matter intake but also showed longer time duration of pH below 6.0 in the reticulorumen (on average 299 min/day compared with 99 and 91 min/day for Medium and High groups, respectively). Differences in metabolic, endocrine and reticuloruminal pH responses indicate diverse metabolic adaptation strategies of early-lactation cows to cope with energy deficit postpartum .